Analisis Aplikasi Marbel Huruf Versi Mobile Terhadap Pembelajaran Membaca di Desa Semanding Ponorogo - Karaman, Jamilah; Setyanto, Arief; Sofyan, Amir Fatah (Universitas Nusantara PGRI Kediri, 2018)
The development of technology, especially information and communication technology offers many ease-ease in learning, which allows the shift of learning orientation from the process of presenting various knowledge into the process of guidance in individual exploration of science. Interactive learning media for children who rampant today is a game-based learning pedia is